2019 IEEE 13th International Conference on Compatibility, Power Electronics and Power Engineering (CPE-POWERENG) 2019
DOI: 10.1109/cpe.2019.8862377
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Rating of Three-Core XLPE Submarine Cables Considering the Impact of Renewable Power Generation

Abstract: This paper discusses how to determine the most suitable high voltage alternating current (HVAC) submarine cable in the design phase of new projects. A thermal ladder network method (LNM) is used to analyse the thermal behaviour in the centre of the conductor as the hottest spot of the cable. Based on an approved static cable rating method and thermal cable analysis of transient conditions, applied by a step function with transient time duration greater than one hour, this paper proposes a method for a dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The scale of these variations are such that cables can experience both significant seasonal and, as cable lengths increase ((e.g., >80 km AC [24], >300 km DC) [25]), spatial variations. Despite these potential changes, standard cable design practice routinely considers 10 • C, 12 • C, or, most commonly, 15 • C to be a representative estimate of ambient temperature at cable depth, irrespective of the location of the cable or how it will be operated over a year [26,27]. A rare example of considering proximal ocean bottom temperature measurements [14] demonstrated that the standard assumption was 10 • C lower than that of the summer OBTs, resulting in potentially dangerous cable-operating temperatures.…”
Section: Cable Ampacity Evaluation Environmental Inputs and Shortcomingsmentioning
confidence: 99%
“…The scale of these variations are such that cables can experience both significant seasonal and, as cable lengths increase ((e.g., >80 km AC [24], >300 km DC) [25]), spatial variations. Despite these potential changes, standard cable design practice routinely considers 10 • C, 12 • C, or, most commonly, 15 • C to be a representative estimate of ambient temperature at cable depth, irrespective of the location of the cable or how it will be operated over a year [26,27]. A rare example of considering proximal ocean bottom temperature measurements [14] demonstrated that the standard assumption was 10 • C lower than that of the summer OBTs, resulting in potentially dangerous cable-operating temperatures.…”
Section: Cable Ampacity Evaluation Environmental Inputs and Shortcomingsmentioning
confidence: 99%
“…However, in most of these applications, the actual temperature of the conductor (or at the cable surface) is required, so it must be adequately derived from the DTS measurements. Since the location of the OF is not standardized [16,17], this involves the use of analytical or numerical adjustment methods, becoming a standard equivalent thermal network-based method (ETN) [10,11,13,[18][19][20][21], where the spatially distributed DTS temperature and the cable current are employed as real-time inputs for obtaining the temperatures of the different cable components (conductor, screen/sheath, jacket, etc.). Due to the thermal resistances and capacitances involved, better static and dynamic results are obtained when the OF is installed closer to one of the already existing ETN nodes (screen/sheath, jacket, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well-known that the IEC 60287 standard [18] overestimates the power losses in this type of cables. In this sense, 2D simulations based on the finite element method (FEM) were extensively employed for validating the performance of the ETN [20]. Nevertheless, both [18] and 2D-FEM models lead to important errors due to the simplifying assumptions considered, where relevant aspects regarding TCAC design are not taken into account, such as the twisting of armor wires and conductors.…”
mentioning
confidence: 99%